Stroke and physiological relationships during the incremental front crawl test: outcomes for planning and pacing aerobic training - Almeida, Tiago A. F.; Espada, Mário C.; Massini, Danilo A.; Macedo, Anderson G.; Castro, Eliane A.; Ferreira, Cátia C.; Reis, Joana F.; Pessôa Filho, Dalton M. (Frontiers in Physiology, 2023)
Purpose: This study aimed to evaluate the physiological responses associated with the stroke length (SL), and stroke rate (SR) changes as swimming velocity increases during an incremental step-test. Moreover, this study also aimed to verify if SL and SR relationships to maximal oxygen uptake (VO2max), gas respiratory compensation point (RCP), exchange threshold (GET), and swimming cost can be applied to the management of endurance training and control aerobic pace. Methods: Nineteen swimmers performed an incremental test until volitional exhaustion, with each stage designed by percentages of the 400m (%v400) maximal front crawl velocity. The VO2max, GET, RCP, and the respective swimming velocities (v) were examined. Also, the stroke parameters, SL, SR, the corresponding slopes (SLslope and SRslope), and the crossing point (Cp) between them, were determined.The GET and RCP corresponded to 70.6 and 82.4% VO2max (4185.3±686.1 ml•min-1 ), and VO2 at Cp, SLslope, and SRslope were observed at 129.7, 75.3, and 61.7% VO2max, respectively. The swimming cost from the expected VO2 at vSLslope (0.85±0.18 kJ•m-1 ), vSRslope (0.77±0.17 kJ•m-1 ), and vCp (1.09±0.19 kJ•m-1 ) showed correlations with GET (r = 0.73, 0.57 and 0.59, respectively), but only the cost at vSLslope and vCp correlated to RCP (0.62 and 0.69) and VO2max (0.70 and 0.79).The SL and SR exhibited a distinctive pattern for V ̇O2 response as swimming velocity increased. Furthermore, the influence of SL on GET, RCP, and VO2max suggests that SLslope serves as Swimming stroke and physiological relationships 2 the metabolic reference of heavy exercise intensity, beyond which the stroke profile defines an exercise zone with high cost, which is recommended for anaerobic threshold and aerobic power training. In turn, the observed difference between VO2 at SRslope and GET suggests that the range of velocities between SL and SR slopes ensures an economical pace, which might be recommended to develop long-term endurance. The results also highlight that the swimming intensity paced at Cp would impose a high anaerobic demand, as it was located above maximal aerobic velocity. Therefore, SLslope and SRslope are suitable indexes of submaximal to maximal aerobic paces, while Cp's meaning still requires further evidence.